Using Forms Quizzes to Enhance Students’ Motivation in Language Learning at a Japanese University - Kita, Yoko (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2021)
This study explores the effective utilization of the online program Forms via smartphones to enrich the classroom experience for both students and teachers in two prep classes for the standardized English Test, Eiken. The instructor used Forms to create, distribute, collect, and analyze surveys and quizzes. Students' attitudes toward English and their motivation to learn the language using these tools were examined. Via smartphones, they were given review quizzes that had game-like elements and that gave feedback in real time. Surveys investigating the degree of confidence in learning, the review quizzes, and smartphone usage were also distributed to their smartphones. The results indicate improvement in attitude towards English in general and enhanced confidence.